Association between red blood cell transfusion and bronchopulmonary dysplasia: a systematic review and meta-analysis - Tang, Li; Zhu, Ting Ting; Zhao, Jing (Frontiers in Pediatrics, 2023)
Background: We aimed to determine the association between red blood cell transfusions (RBCT) and bronchopulmonary dysplasia (BPD) in neonates. Methods: A systematic review and meta-analysis were conducted using data obtained from literature search of PubMed, Embase, and Web of Science from their inception till May 1, 2022. Two reviewers independently selected potentially relevant studies, and after data extraction, they assessed the methodological quality of the included studies using the Newcastle–Ottawa scale. Data were pooled using random-eﬀects models in Review Manager 5.3. Subgroup-analysis was performed based on the number of transfusions and adjusted results. Results: Of the 1,011 identified records, 21 total case-control, cross-sectional, and cohort studies were selected, which included a total of 6,567 healthy controls and 1,476 patients with BPD. The pooled unadjusted odds ratio([OR], 4.01; 95% confidence interval [CI] 2.31-6.97) and adjusted OR (5.11; 95%CI 3.11-8.4) showed significant association between RBCT and BPD. A substantial heterogeneity was noted, which could be due to different variables controlled for in each study. The subgroup analysis showed that heterogeneity may be partially explained by the extent of transfusion. Conclusion: The association between BPD and RBCT remains unclear based on the current data due to the substantial heterogeneity among the results. Well-designed studies are still needed in the future.